2016
DOI: 10.1177/2054270415622602
|View full text |Cite
|
Sign up to set email alerts
|

The impact of poor glycaemic control on the prevalence of erectile dysfunction in men with type 2 diabetes mellitus: a systematic review

Abstract: ObjectiveTo determine the impact of poor glycaemic control on the prevalence of erectile dysfunction among men with type 2 Diabetics aged 27 to 85 years.DesignThe databases Embase classic+Embase, Global health, Ovid Medline and PsychINFO, were searched for relevant studies in June 2014 using the keywords: (Diabetes Mellitus OR diabetes mellitus type2 OR DM2 OR T2DM OR insulin resistance) AND (erectile dysfunction OR sexual dysfunction OR impotence) AND glycaemic control.SettingAll study settings were considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 41 publications
7
41
2
5
Order By: Relevance
“…This further supports the relevance of the role of ED ascertainment in assessing risk of Type 2 diabetes. It has been reported that ED is a Type 2 diabetesassociated factor [3], with even higher prevalence where metabolic control is not optimal [13]. In men with Type 2 diabetes who are aware of their condition this could signal insufficient treatment or low adherence.…”
Section: Results Interpretationmentioning
confidence: 99%
“…This further supports the relevance of the role of ED ascertainment in assessing risk of Type 2 diabetes. It has been reported that ED is a Type 2 diabetesassociated factor [3], with even higher prevalence where metabolic control is not optimal [13]. In men with Type 2 diabetes who are aware of their condition this could signal insufficient treatment or low adherence.…”
Section: Results Interpretationmentioning
confidence: 99%
“…Some studies have observed association between poor glycaemic control as expressed by elevated levels of glycosylated haemoglobin whist other studied did not report any association (Esposito, Maiorino, and Bellastella 2014). Further research is required to clarify causal link between prolonged hyperglycaemia and erectile dysfunction (Binmoammar et al 2016).…”
Section: Discussionmentioning
confidence: 94%
“…The male participants had an International Index of Erectile Function (IIEF-5) Questionnaire administered on them by a male medical doctor. Erectile dysfunction scores of 22 to 25 were classified as no erectile dysfunction where as a score of 21 and below were classified as erectile dysfunction (Shi et al 2014) (Binmoammar et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Diyabetik hastalarda ED, diyabetik olmayan erkeklerden 10-15 yıl önce ortaya çıkmaktadır (3,4). Diyabetik erkeklerde ED un daha ciddi olduğu ve daha kötü yaşam kalitesi ile ilişkili olduğu gösterilmiştir (5).…”
Section: Introductionunclassified